2023
DOI: 10.1038/s41586-022-05590-4
|View full text |Cite
|
Sign up to set email alerts
|

Early Release Science of the exoplanet WASP-39b with JWST NIRCam

Abstract: Measuring the metallicity and carbon-to-oxygen (C/O) ratio in exoplanet atmospheres is a fundamental step towards constraining the dominant chemical processes at work and, if in equilibrium, revealing planet formation histories. Transmission spectroscopy (for example, refs. 1,2) provides the necessary means by constraining the abundances of oxygen- and carbon-bearing species; however, this requires broad wavelength coverage, moderate spectral resolution and high precision, which, together, are not achievable w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(69 citation statements)
references
References 127 publications
5
63
1
Order By: Relevance
“…CO remained undetected with the Bayesian fitting analysis and therefore we are unable to robustly confirm evidence of CO. Similarly, no evidence for CH 4 was found 23 . Gaussian residual fitting in the region of CH 4 absorption only found a very broad inverse Gaussian and so is not included in ED Table 3.…”
Section: Extended Datamentioning
confidence: 92%
See 2 more Smart Citations
“…CO remained undetected with the Bayesian fitting analysis and therefore we are unable to robustly confirm evidence of CO. Similarly, no evidence for CH 4 was found 23 . Gaussian residual fitting in the region of CH 4 absorption only found a very broad inverse Gaussian and so is not included in ED Table 3.…”
Section: Extended Datamentioning
confidence: 92%
“…To quantify the statistical significance, we performed two different tests. First, we used a Gaussian Residual Fitting analysis, as used in other JTEC ERS analyses 23,29,32 . In this method, we subtracted the best-fit model without a specific opacity source from the weighted average spectrum of WASP-39b, isolating the supposed spectral feature.…”
Section: Picaso 30 and Virgamentioning
confidence: 99%
See 1 more Smart Citation
“…NGTS and TESS photometric monitoring of WASP-39A is reported in ref. 23, which finds low modulations at the 0.06% level with no apparent star-spot crossings. With low stellar activity levels, the transit observations are unlikely to be affected by stellar activity.…”
Section: Stellar Activitymentioning
confidence: 97%
“…JWST observations of exoplanet atmospheres have started to reveal absorption by carbon-and oxygen-bearing species at unprecedented precision. Recent measurements of the Saturnmass hot Jupiter WASP-39b (Faedi et al 2011) showed the definitive detection of carbon dioxide (CO 2 ; Alderson et al 2023;Rustamkulov et al 2023; The JWST Transiting Exoplanet Community Early Release Science Team et al 2023) and water (H 2 O; Ahrer et al 2023;Alderson et al 2023;Feinstein et al 2023;Rustamkulov et al 2023), with additional absorption from photochemically generated SO 2 (Tsai et al 2022;Alderson et al 2023;Rustamkulov et al 2023). The lowresolution, R ∼ 100, Near Infrared Spectrograph (NIRSpec) PRISM observations additionally hinted at the presence of broadband absorption due to carbon monoxide (CO; Rustamkulov et al 2023).…”
Section: Introductionmentioning
confidence: 99%